A assistência odontológica no SUS na perspectiva do usuário e o direito à saúde bucal - Luciara Leao Viana (2014)
INTRODUCTION: Bioethics, in its approach linked to public health, aims to be a practical instrument for the defense of citizenship, human rights and social justice. However, regarding health care, their assumptions include possible financial and institutional limits for effective coverage of the population. In Brazil, the quality of the health care offered by the Unified Health System (SUS) does not meet the demand, especially with regard to specialized procedures. Regarding oral health, despite the reduction in the prevalence of dental caries in Brazil, the difficulty in accessing dental care persists, especially among adults. METHODOLOGY: A Literature review on Bioethics on Public Health and its applications in the current scenario was performed in Brazil, seeking to build a bottom line for research on the status of dental care in the perspective of users, their needs and perceptions of the care provided. Then, a qualitative research was done using the technique of semi-structured interviews with 15 female users of public dental care system of the city of Diamantina, Minas Gerais. The data collected was analyzed using the content analysis, taking as a theoretical propositions the symbolic interactionism of Erving Goffman and Bourdieu's concept of habitus. RESULTS: Most people described negatively their teeth situation, possibly due to their poor living conditions in childhood and adolescence and the lack of access to dental care, unless tooth extraction. Decayed, ugly or missing teeth are a reason of shame for them and deprivation in social relations. The social value of the tooth overlaps the strict health aspect. To date, users have no access to specialized treatment in the public system. CONCLUSION: The right to oral health and well-being in society are still an illusion for women in this research. They even envision the possibility of having access to dental care to recover the good appearance of the mouth.